Perkembangan E-LKPD Sebagai Sumber Belajar Praktek Sholat Pada Mata Pelajaran PAI Kelas V di SD Negeri 03 Pakan Labuah - Rihan Mitia; Supratman Zakir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
One of the media used by PAI teachers at SDN Pakan Labuh 03 is Student Worksheets (LKPD) in learning, especially in Islamic Religious Education lessons. The teacher only gives an explanation of the material then practices the prayer movement directly, then evaluates it. This teaching method is considered inappropriate, because there are still many students who have difficulty understanding the concept of good and correct movement according to Islamic law. The existence of the development of LKPD into e-LKPD that supports the learning of Islamic Religious Education prayer practice materials with the aim of this research is to produce valid, practical, and effective e-LKPD to train students' prayer movements (psychomotor) according to Islamic law on prayer practice material.This research is a development research which has 4 stages, namely: define stage, design stage and develop stage, socialization stage. The research instrument uses product tests, namely: product validity test, product practicality test, and product effectiveness test. The E-LKPD was validated by three validators, namely one media lecturer, one PAI lecturer, and one PAI teacher. At the practicality stage, e-LKPD as a learning resource for prayer practices was tested on fifth grade students at SD Negeri 03 Pakan Labuh.The results of this study are E-LKPD with the support of Liveworksheet and Canva Apps get a final validation value of 0.84, a final practicality value of 0.85 and a final effectiveness value of 0.86. It can be concluded that the development of E-LKPD as a Learning Resource for Prayer Practices at SD Negeri 03 Pakan Labuh is very valid, very practical and very effective to use. E-LKPD can increase teacher creativity, so that ELKPD will look interactive, fun and attract students' learning interest. Interactive E-LKPD is synonymous with sheets in the form of student practice questions done through digital media that meet standards, are practical, and are easily accessible.